THE EFFECTS OF ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURIAL INTENTIONS AND THE MODERATING EFFECT OF ENTREPRENEURSHIP POLICY IN THE UNITED ARAB EMIRATES (UAE) - Al-Ameri, Abdullah; Rosdi, Siti Asma Mohd (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
The research study examined the association between Entrepreneurship Education and Entrepreneurial intentions of young people in Education with its moderating variable of Government Entrepreneurship policy in Abu Dhabi in the United Arab Emirates (UAE). The research study adopted a quantitative study approach based on a survey research design and survey data of 320 respondents who were mostly of the age group of young adult students pursuing business and related courses. The research study utilised simple random sampling strategy to garner data from the field in Abu Dhabi in order to avoid bias and to give each participant equal chances of being selected to belong to the study. Data was analysed using Structural Equation Modelling (SEM) and Correlation Matrix (Pearson) in order to establish the relationship between the study variables. The findings indicated that Entrepreneurship Education has a significant positive effect on Entrepreneurial Intentions, and the positive direct effect was also observed in government’s supportive entrepreneurship policies of funding students’ business projects. Besides, the moderation analysis indicated the fact that the relationship between Entrepreneurship Education and Intentions is intensified with the assistance of government’s policy support. The research study concluded that Entrepreneurship Education plays a vital role in the process of developing Entrepreneurial Intentions. Long-term exposure to Entrepreneurship Education, especially when presented in a well-designed and relevant curriculum has been found to make significant impacts in changing the intentions of students towards taking part in entrepreneurial behaviour and also developed the long-term entrepreneurial attitudes. This is because the learners are able to acquire knowledge, skills, confidence, and a positive attitude to undertake Entrepreneurship activities for development. Since the study is based on empirical evidence obtained from the field in Abu Dhabi, the findings are generalisable to all other regions in the UAE. The study recommends that government should augment on the funds allocated to entrepreneurship groups for improving their businesses and fostering entrepreneurial mindsets of the young people in Education in the UAE.